Mewujudkan Citra Pemimpin Abad Ke-21 Bertolak Pada Ajaran Astha Brata Untuk Masa Depan Kabupaten Nganjuk - Siti Musa’adah; Akhmad Arif Musadad; Sudiyanto Sudiyanto (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this study is to find out and examine the existing leadership Nganjuk Regency, as for the formulation of the problem to be discussed, namely 1) what is the defenition of leadership?, 2) how is the concept of Astha Brata teachings?, 3) how is the image of the Nganjuk Regent’s leadership based on Astha Brata teachings?, research using a qualitative methodology with a literature study appoach. The findings show that leaders in Nganjuk Regency don’t yet have and apply the leadership attitudes that exist in the teaching of the Astha Brata, leaders often abuse power, to improve the image of the Nganjuk leadershio, it is necessary to reorganize so that the same case does’nt happen again.